Cross-talk among epigenetic modifications: lessons from histone arginine methylation. (23rd May 2013) - Molina-Serrano, Diego; Schiza, Vassia; Kirmizis, Antonis
Abstract : Epigenetic modifications, including those occurring on DNA and on histone proteins, control gene expression by establishing and maintaining different chromatin states. In recent years, it has become apparent that epigenetic modifications do not function alone, but work together in various combinations, and cross-regulate each other in a manner that diversifies their functional states. Arginine methylation is one of the numerous PTMs (post-translational modifications) occurring on histones, catalysed by a family of PRMTs (protein arginine methyltransferases). This modification is involved in the regulation of the epigenome largely by controlling the recruitment of effector molecules to chromatin. Histone arginine methylation associates with both active and repressed chromatin states depending on the residue involved and the configuration of the deposited methyl groups. The present review focuses on the increasing number of cross-talks between histone arginine methylation and other epigenetic modifications, and describe how these cross-talks influence factor binding to regulate transcription. Furthermore, we present models of general cross-talk mechanisms that emerge from the examples of histone arginine methylation and allude to various techniques that help decipher the interplay among epigenetic modifications.